Geographic Distribution of Cancer Care Providers in the Philippines - Michelle Ann B. Eala; Ethan Angelo S. Maslog; Edward Christopher Dee; Frederic Ivan L. Ting; Jean Anne B. Toral; Rodney B. Dofitas; Henri Cartier S. Co; Johanna Patricia A. Cañal (JCO Global Oncology, 2022)
PURPOSEIn the Philippines, a lower middle-income country in Southeast Asia, 6 of 10 Filipinos die without seeing a doctor. To ensure universal access to cancer care, providers must be equitably distributed. Therefore, we evaluated the distribution of oncologists across all 17 regions in the Philippines.METHODSWe gathered data from the official websites of national medical societies on their members' regional area of practice: Philippine Society of Medical Oncology, Philippine Radiation Oncology Society, Surgical Oncology Society of the Philippines, Society of Gynecologic Oncologists of the Philippines, and Philippine Society of Hospice and Palliative Medicine. We compared this with the regional census to determine the number of board-certified oncologists per 100,000 Filipinos.RESULTSFor a population of almost 110 million, the Philippines has a total of 348 medical oncologists, 164 surgical oncologists, 99 radiation oncologists, 142 gynecologic oncologists, and 35 hospice and palliative medicine (HPM) specialists. This translates to 0.32 medical oncologists, 0.15 surgical oncologists, 0.09 radiation oncologists, 0.13 gynecologic oncologists, and 0.03 HPM specialists for every 100,000 Filipinos. The number of oncologists is highest in the National Capital Region in Luzon and lowest in the Bangsamoro Autonomous Region in Muslim Mindanao. All regions have at least one medical and gynecologic oncologist. Two regions (12%) have no surgical oncologists, five regions (29%) have no radiation oncologists, and eight regions (47%) have no HPM specialists.CONCLUSIONEfforts are needed to increase the number of oncologists and improve equity in their distribution to ensure universal access to cancer care in the Philippines.